Efficacy in the use of local anesthesia in patients with surgical intervention for the resolution of anorectal pathologies - Dowling,Victoria (2018)
ABSTRACT A prospective, comparative, longitudinal study was conducted in the period from April 2016 to January 2017 in order to determine the efficacy of local anesthesia for the surgical resolution of anorectal pathologies in surgically operated patients who attended the General University Hospital “Luis Gomez Lopez. Thus, the population was composed of patients with anorectal pathologies of low complexity, with no previous anorectal surgical history (Hemorrhoids, anal fissure, perianal fistula, hypertrophic anal papilla, perianal condyloma acuminata), which were agreed to be included in this study, without contraindications for use of local anesthesia. A non-probabilistic, intentional sample was made up of 30 patients and the anesthetic protocol was administered following an anesthetic protocol of perianal local anesthesia using anesthetic mixture (70% of 2% lidocaine + 30% of 0.5% bupivacaine) quantifying pain tolerance during the intraoperative period on the first and fifth postoperative days, as well as any adverse effects. The results were expressed in absolute numbers and percentages; a good tolerance to pain was observed with some differences related to the sex of the individuals studied; no complications were observed.